KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA: STUDI ANALISIS META - Fanani, Zaenal (University of Merdeka Malang, 2014)
This study aimed to examine the factors influencing profit management in Indonesia, namely firm characteristicsand good corporate governance. This study used META- analysis technique which was developed byHunter Schmidt (1990) and Lipsey Wilson (2001) by using samples consisting of 12 journals which wereaccredited nationally minimal B. Empirical evidence found that good corporate governance represented byauditor quality, audit committee, management ownership, institutional ownership and independent commissioner,and firm characteristic represented by growth level, firm size, firm performance, firm book value, couldbe the predictor of profit management existence in a company while the other variable namely operation cashcurrent could not be the predictor of profit management in a company.